Luminescence of a Novel Near-UV Emitting Phosphor BaB8O13:Pb2+ - Erdoğmuş, Ertuğrul; Korkmaz, E.; Kafadar, V. Emir; Erdoğmuş, Ertuğrul (Springer, 2014)
Ba1-x Pb (x) B8O13 (0.005 a parts per thousand currency signaEuro parts per thousand x a parts per thousand currency signaEuro parts per thousand 0.0175) phosphors were synthesized by a conventional solid-state reaction using BaCO3 (99.99%), H3BO3 (99.80%), and PbO (99.99%) as starting materials. X-ray powder diffraction (XRD) analysis confirmed the formation of BaB8O13. Measurement of the photoluminescence (PL) excitation spectrum of BaB8O13:Pb2+ shows this phosphor can be efficiently excited by ultraviolet (UV) light from 200 to 280 nm and presents a dominant luminescence band centered at 360 nm. The effects of the doped-Pb2+ concentration in BaB8O13:Pb2+ on the PL were investigated in detail. The results showed that the relative PL intensity increased with increase in Pb2+-concentration reaching until 0.01 mol, where the intensity maximum was reached, and then it decreased due to concentration quenching. The thermoluminescence (TL) properties of BaB8O13 samples with different concentration of Pb2+ were also investigated.
Keywords: Bab8o13:Pb2+; Photoluminescence; Thermoluminescence; Concentration Quenching